Multiplicative Laplace transform in q- calculus - Yilmazer, Mehmet Cagri; Yilmaz, Emrah; Goktas, Sertac; Et, Mikail (Univ Nis, Fac Sci Math, 2023)
In this study, we introduce q*- (or q-multiplicative) Laplace transform by means of q*-integral. Some properties of q*-Laplace transform are presented. Also, q*-Laplace transform can be utilized for solving q*-linear differential equations.
Keywords: Multiplicative calculus; Laplace Transform; Quantum Analysis